The accounting law and the Globalisation Era - LEPĂDATU, Gheorghe (Annals of Spiru Haret University. Economic Series, 2010)
The accounting law appeared as a new procedure together with the globalisation period and the knowledge economy. The accounting information relevance for company patrimony approach is both an economic theoretical issue and an accounting law one. Apart from the norms regarding significance breakeven and economic axiom, contractual aspects are also important. The most precise, organized and significant data can be obtained only from accounting. In this way, managers and administrators would like to get information ignoring the real capacity of accounting as much as possible. For this kind of situations, it is the accounting law that puts things into light.